Transaksi Cryptocurrency di Era Digital: Tantangan, Regulasi, dan Solusi Hukum Ekonomi Islam - Mubarokah, Shela Syofiatul; Yazid, Muhammad (Universitas Islam Lamongan, 2025)
The development of technology is advancing at an increasingly rapid pace. One of these technological developments is the emergence of cryptocurrency in the digital era. Cryptocurrency, as a decentralized digital asset, has rapidly developed and become one of the main financial instruments in the global market. However, from the perspective of Islamic economic law, various issues arise regarding the validity of these transactions, particularly concerning the principles of muamalah jurisprudence such as justice, transparency, avoidance of riba (interest), gharar (uncertainty), and maysir (gambling). This article aims to identify the challenges and solutions of Islamic economic law that can be applied in cryptocurrency in accordance with Islamic principles. This research uses the library research method. The results highlight that while cryptocurrency poses regulatory and ethical challenges, it also offers opportunities for efficiency and inclusion if guided by Islamic principles. The study concludes that adaptive regulation and Islamic economic legal frameworks are essential to ensure transparency, fairness, and justice in digital finance.